2021
DOI: 10.1108/jes-09-2021-0462
|View full text |Cite
|
Sign up to set email alerts
|

Does intellectual property rights protection affect UK and US outward FDI and earnings from FDI? A sectoral analysis

Abstract: PurposeDespite decades of research, the relationship between intellectual property rights (IPRs) and foreign direct investment (FDI) remains ambiguous. Using a recently developed patent enforcement index (along with a broader IPR index) and a large sectoral country-to-country FDI dataset, the authors revisit the FDI-IPR relationship by testing the impact of IPRs on UK and US outward FDI (OFDI) flows as well as earnings from outward FDI (EOFDI).Design/methodology/approachThe authors use disaggregated data for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Chen (2021b) included that the production pattern leads to strengthening the protection of INPR and thus increasing the long-term scope of FDI. Glauco et al (2021) indicated that the measure of intellectual property strength is extended for dynamic effects of the response of FDI to both previous investment levels and patent protection. Xu et al (2020) that regional R&D input has a positive impact on the sustainable patent output of small-and medium-sized enterprises (SMEs).…”
Section: Empirical Evidence About Intellectual Property Rights and Te...mentioning
confidence: 99%
“…Chen (2021b) included that the production pattern leads to strengthening the protection of INPR and thus increasing the long-term scope of FDI. Glauco et al (2021) indicated that the measure of intellectual property strength is extended for dynamic effects of the response of FDI to both previous investment levels and patent protection. Xu et al (2020) that regional R&D input has a positive impact on the sustainable patent output of small-and medium-sized enterprises (SMEs).…”
Section: Empirical Evidence About Intellectual Property Rights and Te...mentioning
confidence: 99%
“…In contrast, IPRs alone may insufficiently strong incentives for transnational corporations to invest in a country due to more important factors influencing transnational corporations' FDI decisions (Maskus, 1998; Pi & Song, 2020). Glauco et al (2021) used patent enforcement index and intellectual property index to study the impact of IPR on FDI of USA and OFDI of UK adopting the fixed effects demonstration. They found that national intellectual property protection has little impact on FDI.…”
Section: Literature Reviewmentioning
confidence: 99%